The Correlation between Students' Foreign Language Anxiety and Their Speaking Performance at Speaking Class - Istna Nurul Aflakha (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This study is aimed to know the correlation between students’ foreign language anxiety and their speaking performance, whether or not there is a correlation between them. The research design of this study is quantitative research in form of correlational design. The subjects of this study were 42 students from forth semester students of English Department in Unisma that took speaking 4 class. FLCAS questionnaire that consists of 33 items was used to collect data of students’ foreign language anxiety and the document of students’ midterm test score to know their speaking performance. The result of this study is there is a low negative correlation between students’ foreign language anxiety and their speaking performance, the higher anxiety of students the lower their speaking performance. Keywords: Correlation, foreign language anxiety, speaking